2021
DOI: 10.3389/fphy.2020.617582
|View full text |Cite
|
Sign up to set email alerts
|

Poroelasticity as a Model of Soft Tissue Structure: Hydraulic Permeability Reconstruction for Magnetic Resonance Elastography in Silico

Abstract: Magnetic Resonance Elastography allows noninvasive visualization of tissue mechanical properties by measuring the displacements resulting from applied stresses, and fitting a mechanical model. Poroelasticity naturally lends itself to describing tissue - a biphasic medium, consisting of both solid and fluid components. This article reviews the theory of poroelasticity, and shows that the spatial distribution of hydraulic permeability, the ease with which the solid matrix permits the flow of fluid under a pressu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 104 publications
0
38
0
Order By: Relevance
“…The shear module achieved by reconstructing the biological soft tissue, based on common MRE, cannot be descriptive of the distribution of true solid matrix parameters (Perriñez et al, 2008 ). Furthermore, tumors tend to have shear moduli between one and two orders of magnitude higher than surrounding tissue, which can be interpreted as poroelastic material rather than viscoelastic material (Sowinski et al, 2020 ). Magnetic resonance poroelastography (MRPE) allows the analysis of tissue-poroelastic behavior by distinguishing the mechanical response of the solid matrix from the free extracellular fluid (Perriñez et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…The shear module achieved by reconstructing the biological soft tissue, based on common MRE, cannot be descriptive of the distribution of true solid matrix parameters (Perriñez et al, 2008 ). Furthermore, tumors tend to have shear moduli between one and two orders of magnitude higher than surrounding tissue, which can be interpreted as poroelastic material rather than viscoelastic material (Sowinski et al, 2020 ). Magnetic resonance poroelastography (MRPE) allows the analysis of tissue-poroelastic behavior by distinguishing the mechanical response of the solid matrix from the free extracellular fluid (Perriñez et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…As initial range of values for the liquid phase dynamic viscosity µ l , we keep different estimation provided in [47] for cerebral fluid, between 0.7 • 10 −3 Pa • s and 1 • 10 −3 Pa • s. For the rheology of the glial phase, as we do not have experimental data, we choose a value close to literature used for generic cells (see [34] and [37]) µ g ≈ 30 Pa • s.…”
Section: Assumption On the Porous Medium Components And Parameters Mo...mentioning
confidence: 99%
“…The important difficulty to design experiment on living tissue and the preferential use of single phase solid mechanics rather than poromechanics are probably partly responsible for this problem. In 2021, Sowinski et al [47] reported ranges of values for hydraulic conductivity K, using in silico magnetic resonance elastography. They reported hydraulic conductivity values from 2 • 10 −11 ms −1 to 2 • 10 −10 ms −1 .…”
Section: Assumption On the Porous Medium Components And Parameters Mo...mentioning
confidence: 99%
See 1 more Smart Citation
“…All the details are provided in [41]. This article allows for reducing the range the mechanical parameters of cortex tissue provided in the literature [61, 62, 63], and more specifically in the poromechanical literature [64, 56]. Although individual variation could be considered, these parameters are related the general mechanical behavior of healthy tissue.…”
Section: Introductionmentioning
confidence: 99%